PENDEKATAN PSIKO-PEDAGOGIS PADA PROGRAM REHABILITASI ODGJ - Salwa Novita Azahra; Yahdinil Firda Nadhirah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The treatment of People with Mental Disorders (ODGJ) requires more than medical intervention; it also involves psycho-pedagogical approaches that emphasize psychological, social, and spiritual development. This study aims to analyze the application of psycho-pedagogical approaches in the rehabilitation program of ODGJ implemented by the Social Service of Lebak Regency. The research method used is descriptive qualitative, with data collected through field observations, interviews, and documentation. The findings show that rehabilitation is carried out through several stages: case identification, initial medical treatment, and follow-up programs in partner rehabilitation institutions. The psycho-pedagogical approach is reflected in emotional counseling, life skills training, and spiritual guidance that strengthens patients’ motivation. The main challenges include the limited number of professionals and persistent social stigma. In conclusion, the psycho-pedagogical approach is proven relevant in restoring the social functions of ODGJ, but stronger budget support, expert capacity-building, and community empowerment are needed to ensure program sustainability.